An international multicenter efficacy and safety study of IqYmune in initial and maintenance treatment of patients with chronic inflammatory demyelinating polyradiculoneuropathy: PRISM study. Issue 4 (31st August 2020) - Nobile‐Orazio, Eduardo; Pujol, Sonia; Kasiborski, Fabrice; Ouaja, Rabye; Corte, Gilles Della; Bonek, Robert; Cocito, Dario; Schenone, Angelo
Abstract: This prospective, multicenter, single‐arm, open‐label phase 3 study aimed to evaluate the efficacy and safety of IqYmune in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Patients received one induction dose of 2 g/kg and then seven maintenance doses of 1 g/kg at 3‐week intervals. The primary endpoint was the responder rate at the end of study (EOS), defined as an improvement of ≥1 point on the adjusted inflammatory neuropathy cause and treatment (INCAT) disability scale. The responder rate was compared with the responder rate of a historical placebo group (33.3%). Secondary endpoints included changes from baseline to EOS of adjusted INCAT disability score, grip strength, Medical Research Council (MRC) sum score, Rasch‐modified MRC sum score, Rasch‐built overall disability scale score and the clinical global impression. Forty‐two patients, including 23 Ig‐naïve and 19 Ig‐pre‐treated, were included in the efficacy set. The overall response rate at EOS was 76.2% (95% confidence interval [60.5%‐87.9%]). The superiority of IqYmune compared to the historical placebo control was demonstrated ( P < .0001). The responder rate was numerically higher in Ig‐pre‐treated than in Ig‐naïve patients but confidence intervals were overlapping (84.2% [60.4%‐96.6%] vs 69.6% [47.1%‐86.8%]). All secondary endpoints confirmed this conclusion. The median time to response was 15 weeks [8.9‐19.1 weeks]. A total of 156 adverse events including five serious were considered related to IqYmune, 87.2% were mild. Neither hemolysis nor signs of renal or hepatic impairment were observed. These results demonstrate that IqYmune is an effective and well‐tolerated treatment in patients with CIDP.